Imposto sobre a renda e indenizações - Bellucci, Maurício (2008)
This work is aimed at examining scientifically if the indemnifications that one receives fit to the legal rule (regra-matriz) of income tax incidence. It justifies itself because the solution and foundation presented by the doctrine and jurisprudence is not uniform. To do so, it presents an income conception based on the legislation and doctrine and confronts it with the theme of moral and material damages repairing. It shows that such a question must be solved according to superior rules presented by the Brazilian Constitution. In the light of law general theory, of philosophy of law, and of semiotics, this work suggests some criteria to be followed by the agent that applies tax law when evaluates economic events related to damage repairing. It concludes that indemnifications do not fit to the materiality of income tax